Respiratory, cardio-metabolic and neurodevelopmental long-term outcomes of moderate to late preterm birth: not just a near term-population. A follow-up study - Alonso-Lopez, Patricia; Arroyas, Maria; Beato, Maite; Ruiz-Gonzalez, Sara; Olabarrieta, Iciar; Garcia-Garcia, Maria Luz (Frontiers in Medicine, 2024)
Introduction. Moderate-to-late preterm infants constitute the majority within the preterm infant population. Most research on preterm infants has focused on very preterm children, often treating moderate-to-late preterm infants as similar to full-term infants. Our objective was to compare clinical, respiratory, cardio-metabolic and neurodevelopmental outcomes in adolescents aged 12-15 years born moderate and late preterm with a control group of the same age born full-term.Observational cross-sectional study, comparing moderate-to-late preterm (32-36 +6 weeks' gestational age) with full-term adolescents (37-41 +6 weeks' gestational age) (75 each group). Perinatal and neonatal history were collected as well as data on respiratory evolution (ISAAC questionnaire for asthma symptoms for adolescents 13-14 years), anthropometric values, learning difficulties, behavioral test (screening questionnaire for high-performance autism spectrum disorder and evaluation test for attention deficit hyperactivity disorder), skin prick test, pulmonary function test, echocardiogram and blood pressure. A blood test with metabolic profile was conducted.Results. Moderate-to-late preterm adolescents had more current asthma [p=0.008, OR3 (95% CI 1.26-7.14)] and longer duration of combined treatments to control asthma (inhaled corticosteroids and anti-leukotrienes) (p=0.048). Forced vital capacity <80% was detected more often in moderate-to-late preterm patients (p=0.013). When assessing right ventricle, moderate-to-late preterm adolescents showed better tricuspid annular plane systolic excursion z-score (p=0.003), shortening fraction (p<0.001) and E/A ratio z-score (p=0.002). Regarding left ventricular assessment, moderate-to-late preterm group had smaller ventricle diastolic diameter (p=0.04) and lower posterior wall z-score values (p=0.037). They also showed a better S´wave z-score (p=0.027), E wave (p=0.005), E/A ratio (p=0.003) and a higher septal myocardial performance index z-score (p=0.025). Moderate-to-late preterm adolescents presented lower weight z-score (p=0.039), body mass index z-score (p=0.013), Waterlow weight index (p=0.006) and higher undernutrition index [p=0.04; OR 1.4 (95% CI 1-1.9)]. Although there were no differences in neurodevelopmental survey or behavioral tests. Conclusion. Our findings underscore the importance of extended follow-up for this predominant group of premature infants to identify potential respiratory, cardiac and anthropometric issues that may emerge in the future.